Legal and Contractual Conditions: Implications on contructors' solvency - Ramachandra, T; Rotimi, JO (Research Publishing Services, 2011)
Often legal and contractual conditions stipulate payment terms for contracts which could impact on constructors’ solvency. Evidence from different countries suggests that legal and contractual conditions have evolved or are evolving to cater for cash flow problems that could lead to insolvencies. However the review shows that in most countries payment terms specified in legislation are applicable only where contractual conditions have not been specified, while in some countries contract conditions become void if they violate legislative provisions. The UK Act requires fair payment regimes and adjudication to be in the contracts. Similarly, NSW and other Acts voids contract provisions that exclude payment rights. Some of the legislation provides distinct features which could be considered upon contracting. For example the Queensland Act provides different payment due time for head contractors (within 25 business days of claim served) and subcontractors (within 15 business days of claim served). The Act of Western Australia and Northern Territory prohibits existing contract provisions of payment within 50 days of a served claim. Similarly, the latest Tasmanian Act prohibits the right to suspend the work if the party fails to make the adjudication within the stipulated time. The paper suggests that appropriate provisions of legislation need to be incorporated into contractual conditions since legislative provisions stand secondary to contract and available by default.
Keywords: Constructors’ solvency; Legislation; Contract conditions; Payment terms